Neurobiology of Acute and Chronic Stress: Its Effect on the Hypothalamo- Pituitary-Adrenal Axis and Memory - Rodríguez-Fernández, Jorge Mario; Yale University School of Medicine (Pontificia Universidad Javeriana, 2013)
Extensive literature has been published about stress and its effects. This paper will focus on how stress hormones interact with different brain areas, including limbic structures and the hypothalamo-pituitary-adrenal axis. We will discuss how repetitive stress modifies those areas, mainly by the effect on its two types of nuclear receptors, changing the basal activity of the amygdala, hippocampus and the medial prefrontal cortex, resulting in an increased hypothalamo-pituitary-adrenal axis function and impairing cognitive functions like memory. The exact mechanism by which these effects are produced is poorly understood. Future research will link how the the cellular and molecular changes described might affect a behavior..